Ratzinger y los filósofos. De Platón a Vattimo. - Antúnez, Jaime (Humanitas (07172168))
The article "Ratzinger and the philosophers. From Plato to Vattimo" highlights the dialogue of theologian Joseph Ratzinger with twenty philosophers of the 20th century, analyzing his theological reflection. The book brings together twenty young specialists in philosophy who study Ratzinger's work, addressing topics such as positivism, existentialism, and the relationship with contemporary philosophers such as Josef Pieper and Robert Spaemann. The importance of the mutual dependence between theology and philosophy throughout history is emphasized.